Implementing TOPSIS method in selecting the best bus transportation services / Azmi Abu Seman, Nasuha Alias and Norfiza Ibrahim - Abu Seman, Azmi; Alias, Nasuha; Ibrahim, Norfiza (UiTM Cawangan Perlis, 2020)
Public transportation using express bus services are widely used by the public nowadays and many bus companies offer services to major cities as well as providing additional features and facilities to attract passengers. However, the passengers often face a problem in selecting the bus companies that give the best services for them according to their preferences. The purpose of this study is to develop a web application system that assists passengers in selecting the best bus services. The web application development follows the System Development Life Cycle (SDLC) methodology that contains four phases which are planning, designing, testing and implementing using PHP and MySQL database as tools for development. In order to get the best result, the application manipulates the MCDM approach using TOPSIS method. It enables users who already used the bus services to give the rating for each criterion and the users who want to use the bus services give their priority for each criterion. Based on TOPSIS rules, the web application will generate the result, which recommends the best bus transportation service for that particular user based on the input related to their preferences for each criterion. Usability testing is carried out in order to get feedback from the user, thus some refinements have been made to the interface of the system. User acceptance test was conducted after the refinement process. After the result was evaluated and analysed, it is shown that most of the components in the web application are well accepted by the respondents. The presence of this web application can help society to choose the best bus services that follow their preferences.